Pyrodinium bahamense One the Most Significant Harmful Dinoflagellate in Mexico - Morquecho, Lourdes (Frontiers in Marine Science, 2019)
Pyrodinium bahamense produces saxitoxins and can cause paralytic shellfish poisoning (PSP). This species has caused more human illnesses and fatalities than any other toxic dinoflagellate in Mexico. The distribution of dinoflagellate cysts with their vegetative stage is wide, mainly along Mexican Pacific coasts, from the central Gulf of California to Chiapas; and, in the southern Gulf of Mexico, and the Mexican Caribbean Sea on the Atlantic coast. Cysts, from southern, Gulf of California exhibit thermophilic (20°C to 35°C) and euryhaline characteristics. Blooms occurred typically during summer rainy season, inside of restricted shallow lagoons surrounded by mangrove forests. The local strain toxicity has only been corroborated in one isolate from the southern Gulf of California, which exhibited a high saxitoxin concentration of 95 pg STX eq cell-1. After dinoflagellate blooms, the PSP outbreaks linked with P. bahamense in the Gulf of Tehuantepec, caused at least ~267 human intoxications, and ~21fatalities from 1989 to 2010. This mini-review ends with a viewpoint of management and research strategies to better understand the factors that play essential roles in the bloom dynamics and toxicity of this species.